Ambulatory Multi-Drug Resistant Tuberculosis Treatment Outcomes in a Cohort of HIV-Infected Patients in a Slum Setting in Mumbai, India - Isaakidis, Petros (Public Library of Science, 2011)
BACKGROUND: India carries one quarter of the global burden of multi-drug resistant TB (MDR-TB) and has an estimated 2.5 million people living with HIV. Despite this reality, provision of treatment for MDR-TB is extremely limited, particularly for HIV-infected individuals. Médecins Sans Frontières (MSF) has been treating HIV-infected MDR-TB patients in Mumbai since May 2007. This is the first report of treatment outcomes among HIV-infected MDR-TB patients in India. METHODS: HIV-infected patients with suspected MDR-TB were referred to the MSF-clinic by public Antiretroviral Therapy (ART) Centers or by a network of community non-governmental organizations. Patients were initiated on either empiric or individualized second-line TB-treatment as per WHO recommendations. MDR-TB treatment was given on an ambulatory basis and under directly observed therapy using a decentralized network of providers. Patients not already receiving ART were started on treatment within two months of initiating MDR-TB treatment. RESULTS: Between May 2007 and May 2011, 71 HIV-infected patients were suspected to have MDR-TB, and 58 were initiated on treatment. MDR-TB was confirmed in 45 (78%), of which 18 (40%) were resistant to ofloxacin. Final treatment outcomes were available for 23 patients; 11 (48%) were successfully treated, 4 (17%) died, 6 (26%) defaulted, and 2 (9%) failed treatment. Overall, among 58 patients on treatment, 13 (22%) were successfully treated, 13 (22%) died, 7 (12%) defaulted, two (3%) failed treatment, and 23 (40%) were alive and still on treatment at the end of the observation period. Twenty-six patients (45%) experienced moderate to severe adverse events, requiring modification of the regimen in 12 (20%). Overall, 20 (28%) of the 71 patients with MDR-TB died, including 7 not initiated on treatment. CONCLUSIONS: Despite high fluoroquinolone resistance and extensive prior second-line treatment, encouraging results are being achieved in an ambulatory MDR-T- program in a slum setting in India. Rapid scale-up of both ART and second-line treatment for MDR-TB is needed to ensure survival of co-infected patients and mitigate this growing epidemic.